The Role Of Counseling Guidance Teachers In Increasing Student Learning Motivation In The Digital Era - Surbakti, Wahyu Persadanta; Hasibuan, Uli Makmun (Journal of Innovation in Research, Education and Culture (JIREC), 2024)
This study aims to understand the role of guidance and counseling (BK) teachers in improving students' learning motivation in the digital era, as well as identify factors that hinder this role. The scope of the research includes analyzing students' needs in the digital context, counseling teachers' ability to integrate technology, and effective strategies to support students' learning. The method used in this research is a literature study by collecting and reviewing literature data which is then connected to the research to get answers to problems obtained from various journals and online books. The results show that counseling teachers have an important role in motivating students by utilizing digital technology to provide more personalized and effective guidance. However, there are some barriers such as limited access to technology and lack of training for counseling teachers. In addition, factors such as parental involvement and the availability of educational facilities also affect the role of counseling teachers in improving students' learning motivation. Nonetheless, this study confirms that a deeper understanding of the role of counseling teachers in the context of digitalization is needed to ensure students get maximum support in their learning process.Keywords: Learning Motivation, Digital Age, Role of Counseling Teacher.